Knowledge of and Attitude towards Female Genital Mutilation among Mothers inAdeoyo Specialist Hospital, Ibadan (2021)
This study investigated mothers' knowledge of and attitudes toward female genital mutilation at Adeoyo Specialist Hospital in Ibadan's postnatal clinic. The descriptive research design was adopted. A total of fifty (50) subjects were used as the sample, and the data far this study were collected using a self-administered questionnaire. In general, (78%) of mothers cited cultural and religious reasons far the practise of female circumcision. Findings showed that mothers had a high level of knowledge, and despite having a high level of knowledge about female genital mutilation and its dangers, the respondents' overall attitude is negative. As a result, social workers will need to increase health education programmes, seminars, campaigns, and rallies to encourage active discouragement of harmful cultural practises, such as female genital mutilation.